A finite element model for compressive ice loads based on a Mohr-Coulomb material and the node splitting technique - Herrnring, Hauke; Ehlers, Sören (Volume 7: Polar and Arctic Sciences and Technology, 2021)
This paper presents a finite element model for the simulation of ice-structure interaction problems, which are dominated by crushing at low and medium confinement ratios. The failure mode of ice depends significantly on the strain rate. At very low impact velocities the ice behaves ductile, whereas at high velocities the ice reacts in brittle mode. This paper focuses on the brittle mode, which is the dominating mode for ship-ice interactions. A multitude of numerical approaches for the simulation of ice can be found in the literature. Nevertheless, the literature approaches do not seem suitable for the simulation of continuous ice-structure interaction processes at low and medium confinement ratios in brittle mode. Therefore, this paper seeks to simulate the ice-structure interaction with the FE method. To preserve mass and energy as much as possible, the node splitting technique is applied, instead of the often used element erosion technique. The intention of the presented model is not to reproduce individual cracks with high accuracy, because this is not possible with a reasonable element size, due to the large number of crack fronts forming during the ice-structure interaction process. The objective of the here introduced Mohr-Coulomb Nodal Split (MCNS) model is to represent the essential material behavior of ice in a efficient formulation. To validate the findings of the model, the simulated maximum ice forces and contact pressures are compared with experiments.